1.
а)х+7у=2 х+7у=2 8-у+7у=2 6у=-6 у=-1 х=9
х+у=8 х=8-у х=8-у х=8-у х=8+1 у=-1
б)2х+у=11 у=11-2х у=11-2х у=11-2*14 х=14
3х-у=4 3х-11-2х=4 х=14 х=14 у=-17
3.
а)3х-8у=6 * 6х-у=27 6х+27-6х=27 0х=0
3х+7у=21 у=-27-6х у=-27-6х у=-27
* 3х-8у+3х+7у=6+21
6х - у = 27
б)4х+5у=1 * 4х+5у=1 4х+5у=1
5х+7у=5 9х+12у=6 | : 3 ---> 3х+4у=2
* 4х+5у+5х+7у=1+5
9х+12у=6
Разложите на множители многочлен :
х+у-х^3-у^3=x+y- (x+y)(x^2-xy+y^2)=(x+y)(1-x^2+xy-y^2);
Упростите выражение:
(а-3)(а+5)-(2а-5)= a^2+5a-3a-15-2a+5=a^2-10;
Представьте в виде многочлена выражение:
(b-1)^2 (b+2)-b^2(b-3)+3=(b^2+2b+1)(b+2)-b^3+3b^2+3=b^3+2b^2+b+2b^2+4b+2-b^3+3b^2+3=7b^2+5b+5.